Analisis Faktor-Faktor yang Mempengaruhi Kinerja Sistem Informasi Akuntansi pada Badan Perencanaan Pembangunan Daerah Provinsi Sumatra Utara - Salsabila Dwi Ananda; Arnida Wahyuni Lubis; Hotbin Hasugian (Penerbit Goodwood, 2024)
Purpose: This study aims to assess the impact of department head support, user participation in information systems, and the performance of accounting information systems in Bappeda North Sumatra Province. By evaluating these factors, the research seeks to identify key determinants that enhance or impede the effectiveness of information systems within the context of a regional development planning agency. Methodology: A quantitative research approach was adopted, utilizing numerical calculations and statistical analysis conducted with SPSS 24 software. Primary data was collected through structured surveys distributed to relevant personnel within Bappeda North Sumatra Province. Results: The analysis revealed that user participation in information systems significantly impacts system performance, highlighting the crucial role of user engagement in the successful implementation and operation of accounting information systems. Conversely, the study found no significant correlation between department head support and the performance of information systems, suggesting that managerial support alone may not be sufficient to enhance system performance without active user involvement. Limitations: The study is confined to Bappeda North Sumatra Province, which may limit the generalizability of the findings to other regions or organizations. Contribution: This research contributes to the understanding of factors influencing information system performance in regional development planning agencies. It provides valuable insights into the importance of user participation in the effectiveness of accounting information systems, particularly within the context of North Sumatra's provincial government. The findings underscore the need for fostering user engagement and suggest that while managerial support is important, it must be complemented by active user participation to achieve optimal system performance.